Alternatif Deteksi Boraks dengan Ekstrak Kulit Ubi Jalar Ungu Sebagai Bahan Praktikum - S Sulistyawati; Widyaningsih Wiyati (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Borax is dangerous for health because it can cause kidney, liver and central nervous system dysfunction. The content of borax in food can be qualitatively detected by various methods. These methods include the flame test and turmeric paper test. The aim of this research is to make an alternative for borax detection using purple sweet potato skin extract as a practicum material. This is to reduce the use of chemical reagents. Reagents from natural materials have advantages such as easy to obtain, more economical and do not cause environmental pollution. This research is an experimental research, using tools and materials of purple sweet potato skin, 96% ethanol, aquadest, borax (Na2B4O710H2O), 10% NaOH, concentrated HCl, pH paper, Macherey-Nagel® Turmeric Paper 90747, white tofu and analytical balance. The results of the purple sweet potato peel extract test on tofu samples were compared to tests using turmeric paper as the gold standard. The positive sample contains borax, if there is a change in color to green in the test with purple sweet potato peel extract, and turns red in the test with turmeric paper. From the results of a comparison of the cost of making borax detection, purple sweet potato peel extract is more economical than using turmeric paper and flame tests. It was concluded that purple sweet potato peel extract could be used as a more economical alternative in qualitatively testing borax content in foods.